Respon Pertumbuhan dan Hasil Tanaman Cabe Rawit terhadap Pemberian Beberapa Dosis Kotoran Ayam di Tanah Podsolik Merah Kuning - Fahrudin Fahrudin; Mahdiannoor (Rawa Sains: Jurnal Sains STIPER Amuntai, 2013)
Cayenne pepper or chilli is a fruit vegetable crops needed by the whole society as a flavoring food and medicine. In general, chilli plants can be grown in all types of soil and grow best when growing conditions are met, but the best is in the lowland soil containing sand with good porosity. This study aimed to know (i) the growth and yield response of cayenne pepper extending of multiple doses of the chicken manure fertilizer (ii) the best doses of chicken manure fertilizer on the growth and yield chili in red yellow podzolic soil. The experiment was conducted in the Timbun Tulang Village Batu Mandi District Balangan Regency from June - September 2010, using a randomized block design (RBD) a single factor, with repeated 4 times and the combination of experimental units 7 pieces, so for the entire experiment were 28 experimental plots. The results showed that treatment doses of chicken manure droppings significant effect on plant height age 14 day after planting (DAP), significant effect on plant height ages 21 and 28 DAP, age of the plant starts to flower and plant fresh weight chili. The best treatment for high-growth plant ages 14, 21 and 28 DAP, age starts to flower and fruit fresh weight chili crop is treated k5 (1.4 kg chicken manure fertilizer / planting hole).